Enhancing E-Learning in Vocational Schools: Key Characteristics of Instructional Design - Wijaya, Widia Murni; Syarifah, Liah Siti; David, Thuok (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
This study discusses the adoption of e-learning as an educational innovation to overcome physical limitations between students and teachers, especially in vocational schools. E-learning offers an alternative to conventional learning with time and place flexibility, as well as a student-centered approach. This study employs a qualitative research method with a narrative approach to analyze instructional design in the adoption of e-learning in vocational schools. The study involves 12 teachers, 12 students, and 4 school leaders from public and private vocational schools in Yogyakarta. Data were collected through interviews and analyzed using NVivo software to identify the dominant characteristics of instructional design in e-learning. The three main characteristics found are: well-stored feedback features, opportunities for users to provide feedback, and user authority to access all learning content. The research results show that feedback features in e-learning are crucial for evaluation and interaction between teachers and students. Users can provide feedback in the form of comments, which helps improve students' understanding of the learning material. Additionally, user authority to access e-learning content allows students and teachers to access materials anytime and anywhere, enhancing their flexibility and interest in using e-learning. This study concludes that effective adoption of e-learning in vocational schools can be enhanced through appropriate instructional design, with clear feedback features and access authority. This can address various challenges in vocational education, such as time and place constraints, and help in diversifying students' skills and abilities.